Identifying optimal genetic markers for predicting quantitative measures in neuropsychiatric disorders - O’Meara, Mika Isabella Grace (Stellenbosch : Stellenbosch University, 2025)
O’Meara, Mika Isabella Grace. 2024. Identifying optimal genetic markers for predicting quantitative measures in neuropsychiatric disorders. Unpublished masters dissertation. Stellenbosch : Stellenbosch University [online]. Available: https://scholar.sun.ac.za/handle/10019.1/131878